2019
DOI: 10.1111/ped.13851
|View full text |Cite
|
Sign up to set email alerts
|

Sivelestat sodium hydrate treatment for refractory Kawasaki disease

Abstract: Background There is still no definite treatment for refractory Kawasaki disease (KD). In this pilot study, we evaluated the safety and efficacy of a new protocol consisting of sivelestat sodium hydrate (SSH) combined with additional i.v. immunoglobulin (IVIG) for KD resistant to initial IVIG therapy. Methods This study is a prospective non‐randomized, open‐label and single‐arm study undertaken in a population of refractory KD patients at Chiba University Hospital from December 2006 to March 2016. The subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Sivelestat, a selective neutrophil elastase inhibitor, prevented phorbol myristate acetate-induced acute lung injury [ 193 , 194 ], enhanced coronary blood flow, and ameliorated myocardial damage after myocardial arrest [ 195 ]. Furthermore, it has shown its protective effect in neuromyelitis optica [ 196 ], refractory Kawasaki disease [ 197 ], knee osteoarthritis [ 198 ], steatohepatitis [ 199 ], and systemic inflammation such as burn [ 200 ]. BAY 85-8501, another selective and potent neutrophil elastase inhibitor, has been revealed to reduce pulmonary disease inflammation [ 201 ].…”
Section: Drug Developmentmentioning
confidence: 99%
“…Sivelestat, a selective neutrophil elastase inhibitor, prevented phorbol myristate acetate-induced acute lung injury [ 193 , 194 ], enhanced coronary blood flow, and ameliorated myocardial damage after myocardial arrest [ 195 ]. Furthermore, it has shown its protective effect in neuromyelitis optica [ 196 ], refractory Kawasaki disease [ 197 ], knee osteoarthritis [ 198 ], steatohepatitis [ 199 ], and systemic inflammation such as burn [ 200 ]. BAY 85-8501, another selective and potent neutrophil elastase inhibitor, has been revealed to reduce pulmonary disease inflammation [ 201 ].…”
Section: Drug Developmentmentioning
confidence: 99%
“…The current study showed that anti-ApoA2 may act as an effective therapeutic agent for treating patients with KD. Antibody based drugs, such as infliximab (an anti-human tumor necrosis factor (TNF)-α monoclonal antibody [ 23 , 24 ]), cytokine antagonists (anakinra, interleukin 1 receptor antagonist, IL-1RA [ 25 ]), and immunosuppressants (e.g., mizoribin [ 20 ] and sivelestat [ 26 ]) have recently been suggested as therapeutic agents for patients with IVIg-resistant KD. As the suppression of TNF-α and IL-1RA diminishes the host response to infections, concerns have been raised regarding the safety of administering infliximab to patients receiving live viral vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous immunoglobulin combined with oral aspirin is recognized as Classification I and Evidence levels A, 7 however, the precise mechanism is not clear. Although our knowledge on the efficacy of the NE inhibitor SSH is limited, the results of clinical studies in real‐world settings have been reported 10,11 . Our objective in this reverse translational study was to investigate the effectiveness of SSH by conducting basic studies on the pharmacology of SSH in mice with CAWS‐induced vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Sivelestat sodium hydrate is cheaper and is considered more selective for NE than UTI. 10 Ebata et al 11 have also described the importance of combination treatment with IVIG and SSH for initial IVIG nonresponders; they reported that 62.2% of the non-responders responded to this treatment, with defervescence within 48 h, and the incidence of coronary aneurysm was restricted to 2.2%. These outcomes were superior to those of additional treatment with IVIG alone (10.0%-33.3%).…”
mentioning
confidence: 99%